Clinical and Radiographic Outcomes of Oblique Lumbar Interbody Fusion at 1 Year: A Preliminary Report of a Single Institution Experience - Doyub Kim; Byeongsam Choi; Hae Yu Kim; Sungjoon Lee (Journal of Minimally Invasive Spine Surgery and Technique, 2020)
Objective Oblique lumbar interbody fusion (OLIF) is a minimally invasive surgical technique that is becoming popular due to lowering the risk of lumbar plexus injuries compared to other transpsoas fusion techniques while yielding comparable clinical outcomes. We evaluated the 1-year clinical and radiologic outcomes of OLIF performed in a single institution of Korea. Methods We retrospectively reviewed patients who underwent OLIF for degenerative lumbar spinal disease at our institution between July 2015 and December 2018. Patients with a follow-up period of longer than 1 year were included. Among 36 patients, 22 patients (9 male, 13 female) and 26 surgical levels were analyzed. The patients’ demographic data, surgical procedures, clinical outcomes and complications were reviewed. Results The patients’ mean age was 64 years (range 44-78). Spinal stenosis was the most common pathology. In all cases, the demineralized bone matrix was used for fusion. The disc height and sagittal angle of the index level showed statistically significant increases at the 1-year follow-up (3.5 mm, p<0.001; 5°, p=0.02, respectively), but the foraminal height did not. The 1-year fusion rate was 69.6%. Good clinical outcomes, as evaluated by visual analogue scale pain scores, Oswestry disability index, EQ-5D-3L index and EQ-VAS, were observed throughout the 1-year follow-up period. No serious complications were observed. Conclusion OLIF appears to be a suitable and safe surgical option for treating degenerative lumbar spinal disease. It showed good clinical outcomes in the short-term follow-up. However, close-long term observations would be necessary since the fusion rates were unsatisfactory.